SINISTER CAUSE OF HIGH BONE MINERAL DENSITY ON DUAL ENERGY X-RAY ABSORPTIOMETRY - Razi, Mairah; Hassan, Aamna (Journal of Ayub Medical College Abbottabad, 2016)
Dual energy X-ray absorptiometry (DXA) has an established, well standardized role in the measurement of bone mineral density (BMD). In routine clinical practice, the main focus of bone densitometry is to identify low bone mass for the diagnosis and monitoring of osteoporosis particularly in postmenopausal females and in high risk individuals. Less commonly, elevated BMD can also be seen on routine DXA scanning usually due to degenerative disease. However, a range of other skeletal disorders can also lead to high BMD. Careful recognition of various artefacts and pathologic processes that can falsely elevate the BMD is essential for accurate DXA scan analysis and reporting. We present a case of high BMD in a patient of prostate carcinoma with widespread sclerotic metastases.